Projeto político pedagógico como espaço discursivo na prática social da escola - Barbosa, Samara Wanderley Xavier (2010)
The objects of this research are the discourses of Pedagogical Political Projects (PPP), which are considered discursive arenas, marked by negotiation and power disputes during the process of the project elaboration and implementation, as they become both producers and products of hybrid discourses which circulate in the school environment. In this way, this paper analyses the discourses which constitute the processes of construction and implementation of the PPP in a public school of the municipal school system in the city of João Pessoa, Paraiba, Brazil, taking as a point of departure the voices of managers, teachers and specialized professionals. Critical Discourse Analysis (CDA), based on the theoretical and methodological perspective proposed by Norman Fairclough (2001) was chosen as a research methodology. In addition to that, the paper draws from the theoretical approaches of scholars like MACEDO (2007), PEREIRA (2004, 2007, 2008), SANTOS (2002, 2004, 2005), VEIGA (1998, 2003, 2006) DE ROSSI (2003, 2006), BALL (2001), DALE (2009), who discuss the educational policies and the Pedagogical Political Project, arousing debate around the school environment. The textual and discursive analysis reveals that the discussion of the PPP in the school is an incipient process, presenting problems that derive from the poor participation and to the lack of knowledge about the theme from the part of the subjects. There seems to be, however, commitment and awareness from the part of some of the subjects regarding the need for their participation, considering that the construction of the PPP has autonomy and democratic management as key principles. The results of this research indicate that the PPP is a discursive space permeated by conflicts and negotiations, which are necessary for the process of fostering curricular identity in schools. The conception of PPP revealed in the discourses present the PPP as a discursive practice that cannot be understood by reference just to a document.